Single-pulse all-optical partial switching in amorphous DyxCo1-xand TbxCo1-xwith random anisotropy - Coey, John; Stamenov, Plamen (My University, 2022)
Repeated uniform switching of the magnetization of thin films of ferrimagnetic amorphous Gdx (FeCo)1 x in response to single fast laser pulses is well established. Here, we report unusual toggle switching in thin films of sperimagnetic amorphous Dyx Co 1 x and Tbx Co 1 x with x 0.25 irradiated with single 200 fs pulses of 800 nm laser light. The samples have strong local random anisotropy due to the non-S state rare earth. The compensation temperature of the films is 180 K, and their Curie temperature is 500 K. They are largely switched by the first pulse, and subsequent pulses lead to partial re-switching of a decreasing amount of the irradiated area, with a granular structure of sub- micrometer regions of switched and unswitched material. Individual switched regions about 700 nm in size are observed around the edge of the irradiated spots where the fluence is at the threshold for switching. Results are discussed in terms of a random anisotropy model where the ratio of local anisotropy to exchange is temperature dependent.
PUBLISHED
cited By 0
Keywords: uniform switching; thin films; sperimagnetic amorphous; uniform switching; thin films; sperimagnetic amorphous